Theoretical study of efficiency comparison of Ti (IV) alkoxides as initiators for ring-opening polymerization of ε-caprolactone - Silawanich A. (2017)
© 2016 Elsevier B.V. The initiators used in the ring-opening polymerization (ROP) were theoretically studied. The ROP of ε-caprolactone initiated by Ti (IV) alkoxides were investigated using high level adiabatic mapping B3LYP/LANL2DZ calculations. The initiators were modeled to be four types; Ti (IV) n-propoxide, Ti (IV) n-butoxide, Ti (IV) 2-ethylhex oxide and Ti (IV) t-butoxide, in order to investigate the efficiency of Ti (IV) alkoxides as initiators. The reactivity of modeled initiators was compared with the experimental results and other theoretical work. The calculated results showed that the first step of reaction is the rate limiting step of the ROP. The efficiency of initiators can be ranked as Ti (IV) n-propoxide > Ti (IV) n-butoxide > Ti (IV) 2-ethylhexoxide > Ti (IV) t-butoxide. The calculated results are in good agreement with experimental results.